KAREKTERISTIK PENGETAHUAN INDERAWI AL-KINDI DAN AL-RAZI TENTANG KONSEP PENGETAHUAN ISLAM - M. Tubi Heryandi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
Sensory knowledge is one of the foundational elements in classical Islamic epistemology, receiving significant attention from prominent Muslim philosophers such as Al-Kindi and Al-Razi. This article aims to examine the characteristics of sensory knowledge according to these two thinkers through a qualitative-descriptive approach and historical-philosophical analysis. The findings reveal that Al-Kindi views sensory knowledge as an initial stage in the intellectual process toward higher (rational) knowledge (ta‘aqqul), yet he acknowledges its limitations due to its temporary and material-bound nature. In contrast, Al-Razi considers sensory knowledge a primary foundation for acquiring empirical truth, particularly in the context of science and medicine, emphasizing observation and experimentation. These differing perspectives reflect the dynamic development of epistemological thought within the Islamic philosophical tradition, highlighting Al-Kindi's rationalistic orientation and Al-Razi's empiricist approach to understanding reality. This study contributes to the development of Islamic epistemology by shedding light on the role and limitations of the senses in the pursuit of knowledge